PERIPHERAL PARASITAEMIA AND ITS ASSOCIATION WITH PLASMA CYTOKINES LEVELS IN MALARIA-INFECTED PREGNANT WOMEN IN ABA, ABIA STATE, NIGERIA - Ifeanyichukwu, M.O.; Okamgba, O.C.; Amilo, G.I.; Nwokorie, E.A. (African Journal of Infectious Diseases (AJID), 2017)
Background: Cytokines in pregnant female may not be a normal phenomenon as malarial infection is often associated with strong CD4+ cell activation and up-regulation of pro-inflammatory cytokines. We investigated the relationship between peripheral parasitaemia and plasma levels of cytokines among malaria infected pregnant women in Aba, Abia State, Nigeria. Materials and Methods: A total of 206 non-HIV positive asymptomatic malaria parasitaemic (n=144) and non-parasitaemic (n=62) pregnant women were recruited for this study alongside 80 non-pregnant women who served as positive (n=40) and negative (n=40) controls. Blood samples were aseptically collected from each subject and tested for HIV and malaria parasites using standard methods. Also, plasma levels of cytokines were measured using Th1/Th2 human cytokine ELISA kits (Abcam, UK). Analysis of Variance and Student’s t-test were used for Comparison of groups while Pearson’s Correlation Coefficient was used for tests of association. Results: The results revealed a mean parasite density of 685.56±484.55 parasites/μl of blood. Malaria infected pregnant subjects showed significantly higher levels of IFN-γ, TNF-α, IL-4, IL-6 and IL-10 when compared with their non-infected counterparts (P< 0.05). The cytokines evaluated were higher in moderate parasitaemia than mild parasitaemia. Positive correlation existed between peripheral parasite density (PPD) and IL-4 (r= 0.24, P=0.004), PPD and IL-6 (r = 0.35, P = 0.001) as well as PPD and IL- 10 (r = 0.29, P = 0.001). Conclusion: This study showed that increase in peripheral parasitaemia increased levels of some plasma cytokines (IL-4, IL-6 and IL-10) but not IFN-γ and TNF-α in the malaria infected pregnant women studied.